"Catholic, but not According to the Rules": Assisted Reproduction and Catholic Doctors in Belgium, 1940s–1980s. (4th June 2021) - Claes, Tinne
Abstract : This article elucidates how Catholic doctors in Belgium, a dominantly Catholic country that was home to the largest Catholic university in Europe, creatively handled church teachings on assisted reproduction from roughly the 1940s until the 1980s. Catholic thought on reproductive medicine is mostly represented as restrictive and conservative, but this is not the full picture. On the contrary, this article reveals that many Catholic moralists and physicians looked for loopholes within church teachings, creating 'Catholic' versions of assisted reproductive technologies. A few progressive Catholics fundamentally questioned the authority of the Vatican, justifying donor insemination and in‐vitro fertilisation by means of personalist ethics. By drawing attention to the diverse ways in which Catholics in Belgium negotiated their own moral understandings of assisted reproduction, this article adds a new dimension to recent histories of contraception, which complicate narratives of conflict between religion, science, and sexual liberation.